POLA RELASI PEMERINTAHAN DESA - Condrodewi Puspitasari; Sumarjono; Putera Perdana; Juang Gagah Mardhika (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
This article aims to explores the relationship between the Government of Kalurahan Bleberan and BUM Desa Sejahtera using a governance perspective and a hybrid institution perspective. BUM Desa Sejahtera is one of the successful BUM Desa in Kabupaten Gunungkidul in managing resources so it is interesting to researched using a governance perspective and hybrid institutions. The method used in this research is qualitative with a case study approach. The results of the study show that the relationship between the Government of Kalurahan Bleberan and BUM Desa Sejahtera has been well-systemized and patterned as an embodiment of a governance perspective. The governance model of the relationship that occurs between the two parties is in accordance with the decentralized model which is low political authority but has a high level of democracy. Based on the perspective of hybrid institutions, resource management in Kalurahan Bleberan has also involved stakeholders through continuous engagement between the Government of Kalurahan Bleberan, BUM Desa management, the Rancang Kencono foundation, as well as citizena and those are regulated in formal regulations that bind all parties.